Inverse effects of Arabidopsis NPR1 gene on fusarium seedling blight and fusarium head blight in transgenic wheat. (16th July 2012) - Gao, C.‐S.; Kou, X.‐J.; Li, H.‐P.; Zhang, J.‐B.; Saad, A. S. I.; Liao, Y.‐C.
<x xml:space="preserve">Abstract</x> In this study, the Arabidopsis thaliana NPR1 (non‐expressor of PR genes) gene was integrated into an elite wheat cultivar, and the response of the transgenic wheat expressing NPR1 to inoculation with Fusarium asiaticum was analysed. With seedling inoculation, the transgenic lines showed significantly increased fusarium seedling blight (FSB) susceptibility, whereas floret inoculation resulted in enhanced fusarium head blight (FHB) resistance. Quantitative real‐time PCR revealed that expression of two defence genes, PR3 and PR5, was associated with susceptible reactions to FSB and FHB, whereas the PR1 gene was activated in resistance responses. This inverse modulation by the constitutively expressed NPR1 gene suggests that NPR1 has a bifunctional role in regulating defence responses in plants. Therefore, it is unsuitable for improving overall resistance to FSB and FHB in wheat.